CYBERSECURITY AWARENESS AND DIGITAL EDUCATION: A GLOBAL BIBLIOMETRIC ANALYSIS - Abdollah, Badariah; Zaki , Nurul Izzati Mohd; Mustapa , Shazana (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The increasing importance of cybersecurity in the digital era showcases the demand for enhancing cybersecurity awareness and strengthening digital education, particularly in academic and professional contexts where vulnerabilities often arise from human factors rather than purely technical weaknesses. In spite of the expanding body of literature, there remains a lack of systematic mapping to understand the trends, patterns, and global collaboration in this research domain. This research addresses the gap by performing a bibliometric analysis of publications related to cybersecurity awareness and digital education. Data were collected through Scopus advanced searching using the keywords "cybersecurity," "awareness," and "education," yielding a total of 1,107 documents. To ensure accuracy, OpenRefine was employed to clean and harmonize the dataset, while Scopus Analyzer provided statistical insights into publication growth, sources, authorship, and citation structures. For deeper visualization, the VOSviewer software was applied to generate co-authorship, co-occurrence as well as country collaboration networks. The analysis indicated a consistent increment in publications throughout the past decade, with notable contributions from leading countries like China, the United States, and the United Kingdom, forming distinct clusters of international collaboration. The thematic mapping indicated a strong emphasis on awareness training, educational strategies, and policy integration in digital learning environments. Nine main clusters were identified, reflecting the multidisciplinary nature of the field across computer science, social sciences, and education. These findings enrich the body of knowledge by offering a thorough overview of research progress, highlighting influential authors and institutions, and identifying gaps where future studies can integrate practical awareness frameworks into digital education systems. In conclusion, this study not only underscores the evolution of cybersecurity awareness in education but also offers a roadmap for policymakers, educators, and researchers to foster resilient digital ecosystems.